2005
DOI: 10.7863/jum.2005.24.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Skeletal Muscle Perfusion Using Contrast-Enhanced Ultrasonography

Abstract: Muscle perfusion can be easily and quantitatively assessed with CEUS. Compared with VOP, CEUS allows for a separate analysis of different muscle groups, unaffected by skin perfusion. Its application may be of particular interest in the diagnosis and monitoring of pathologic microvascularization in myositis or diabetic obstructive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 26 publications
5
96
1
1
Order By: Relevance
“…During the exercise, local blood volume decreased but increased rapidly after the exercise stopped as measured by contrast-enhanced sonography. In another study by Krix et al, 5 concentric-eccentric contractions were performed using a hand grip dynamometer for 2 minutes at 65% to 70% maximum maximal voluntary isometric contraction. Blood flow increased 11.2 times (660%) in the biceps muscle after exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the exercise, local blood volume decreased but increased rapidly after the exercise stopped as measured by contrast-enhanced sonography. In another study by Krix et al, 5 concentric-eccentric contractions were performed using a hand grip dynamometer for 2 minutes at 65% to 70% maximum maximal voluntary isometric contraction. Blood flow increased 11.2 times (660%) in the biceps muscle after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] This increase in blood flow is proportional to the metabolic demands of the muscle tissue being exercised. 9 Metabolic demand changes depending on the type of exercise performed.…”
mentioning
confidence: 99%
“…The AI obtained during the first 0.5 sec was averaged and subtracted from the AI recorded during the remaining time to eliminate background noise and contribution from any rapid filling vessels in the ROI. Calculations were made in accordance to Wei et al, with AI vs. time curves fitted to the equation: y = A[1 -e -β(t-β t )], where t is time (s), B t the time used for background subtraction, y is the acoustic intensity at any given t, A is the plateau AI defined as MBV and β is the flow rate constant (1/s) that determines the rate of rise of AI, proportional to microvascular flow velocity (MFV; (Krix et al 2005;Wei et al 1998)). The product of Aβ with the unit volume blood -1 ·volume tissue -1 ·second -1 is proportional to microvascular blood flow (MBF) (Mitchell et al 2013).…”
Section: Microvascular Blood Volume (Mbv)mentioning
confidence: 99%
“…It has been shown that IMCL levels vary with diet and physical activity and it has been reported that IMCL levels are correlated with insulin sensitivity [5]. Furthermore, skeletal muscle microcirculation can be quantified by contrast-enhanced ultrasonography (CEUS) analyzing replenishment kinetics after destruction of intravenously injected microbubbles by ultrasonographic pulses [9,10]. This technique is sensitive enough to allow for detection of the low skeletal muscle perfusion, i.e.…”
mentioning
confidence: 99%
“…the capillary blood flow, at rest [11]. It also allows for quantification of physiologically increased perfusion after exercise [9] and pathologically increased perfusion in inflammatory myopathies [10].…”
mentioning
confidence: 99%